O026 Which place for the NLRP3 inflammasome in the MSU crystal-induced inflammatory response in vivo?. (21st February 2018) - Mariotte, A; Zhang, Z; de Cauwer, A; Frisch, B; Bahram, S; Ricci, R; Georgel, P
Abstract : Introduction: The NLRP3 ( N ucleotide-binding and oligomerisation domain, L eucine-R ich repeat and P yrin containing 3 ) inflammasome is a multiprotein complex made of the NLRP3 sensor, the caspase 1 enzyme and an adaptor, ASC. Upon exposure to sterile or infectious stimuli, the NLRP3 inflammasome assembles and cleaves pro-IL-1β and pro-IL-18 into their bioactive forms. Gout is a common microcrystalline arthritis induced by MSU (M ono-S odium U rate) crystals accumulation which triggers an inflammatory response depending on the NLRP3-IL-1-IL-1R axis in vitro 1 ; however, this relationship is far less understood in vivo . PKD ( P rotein K inase D ) were recently shown as important regulators of the NLRP3 inflammasome. 2 Objectives: To study the in vivo relevance of the PKDs-NLRP3 axis in two mouse models of gout. Methods: Experiments were conducted in mice deficient for NLRP3, for PKD1 and 3 or mice in which PKD1, 2 and 3 were blocked by a pan-PKD inhibitor. Peritoneal macrophages were stimulated by MSU crystals to assess IL-1β production. Gouty arthritis was triggered by subcutaneous injections of MSU crystals in the hind-paws and MSU-induced peritonitis by crystals injection in the peritoneal cavity. Results: We confirmed the absence of IL1β release by MSU-challenged peritoneal macrophages isolated from NLRP3KO animals. Pharmacological pan-PKD inhibition gave similar results, whereas genetic loss of PKD1 and 3 did not. The peritoneal gout model showed a reduction in neutrophils recruitment in NLRP3KO animals, and an increased neutrophils influx in PKD1-3dKO mice. Finally, we did not observe any alteration in gout severity in NLRP3-deficient and pan-PKD inhibitor-treated mice following MSU crystal subcutaneous injections; PKD1-3dKO animals even displayed more severe symptoms in this assay. Conclusions: Our data seem to confirm that the PKD-NLRP3 axis exerts a major role in sensing MSU crystals in vitro but the relevance of this pathway in our in vivo gouty arthritis models is not so clear. We speculate that an alternative pathway could compensate for the loss of IL-1β in NLRP3 inflammasome-deficient mice. Unravelling this possibility might be of major fundamental interest and could even lead to new therapeutics in the field of inflammation. References: . Martinon F, et al. Nature2006. . Zhang Z, et al . J. Exp. Med 2017. Disclosure of interest: None declared